The Prevalence of Dental Fluorosis among Adolescents Aged 12–15 Years in Schools of Ghaziabad, Uttar Pradesh, India - Shilpa Singh; Vikas Singh; Pradeep Tangade; Ankita Jain; Ishmita Jain; Manika Rawat (Journal of Pharmacy and Bioallied Sciences)
Objective: To provide significant insights into the incidence rates, severity levels, and possible risk factors related with dental fluorosis to promote evidence-based public health measures. Materials and Methods: A stratified sampling technique will be conducted on the adolescent patients (12–15 years) attending school in Ghaziabad district, Uttar Pradesh. A sample of 672 students from different schools will be selected for the survey. An informed consent in writing will be collected from the children’s parents those who are willing to participate in the study. Results: The prevalence of fluorosis among sample of 672 individuals reveals that 14.5% exhibit normal Fluorosis Index (FI), while 15.5% exhibit questionable FI, 17% have very mild FI, 23.5% accounts for mild FI, 14.5% exhibit moderate FI, while 15% exhibit severe FI.